Continuous film spin-orbit torque characterization via four probe measurement - Poh, Han Yin (2022)
Spin-orbit torque (SOT) characterization techniques generally require the Hall cross that generally demands lithography resources and time. It is highly desirable to characterize SOT efficiencies with minimal sample processing time. Here, we demonstrate a lithography-free technique to determine the spin-orbit torque efficiency in a perpendicular magnetic anisotropy ferromagnetic heterostructure. By utilizing a customized four-point probe in a rhombus geometry, harmonic Hall measurement was performed on continuous films of a Pt/Co/Ti structure to characterize the spin-orbit torque efficiency. A correction factor, which is due to the non-uniform current distribution across the continuous film, was experimentally evaluated by taking the ratio of the measured damping-like field of the continuous film to that of a fabricated Hall device. Additionally, this correction factor is analytically derived and experimentally shown to be determined by the configuration of the probes and is independent of the structure material. Our measurement reveals that by performing a single calibration process for the particular set of probes, the same correction factor was validated on a second ferromagnetic heterostructure, Ti/Pt/Co/Ta; hence, it can be applied to other SOT films' stack measurements. Our four-probe harmonic Hall technique provides an alternative and swift way for SOT investigations by eliminating multiple lithography processes necessary in conventional approaches.